A Decision Making Learning Model On Class IV Students Writing Skills UPT State Elementary School 060890 Medan Polonia - Fitriani, Dian (Berpusi Publishing, 2023)
This study aims to: (1) Know the writing skills of fourth grade students of UPT SDN 060890 Medan Polonia before using the decision making learning model, (2) Know the writing skills of fourth grade students of UPT SDN 060890 Medan Polonia after using the decision making learning model , (3) Knowing the effect of the decision making learning model on the writing skills of class IV UPT SDN 060890 Medan Polonia students. This type of research is a quantitative study with a one-group pretest-posttest design . The population of this study were all students of class IV UPT SDN 060890 Medan Polonia, totaling 28 people. The sampling technique used is saturated sampling in which all members of the population are used as samples. Data collection techniques using observation sheets. Based on the research results: (1) Before using the decision making learning model , the average score of students was still low, namely 56.18, and the highest score obtained by students before using the decision making learning model was 70, (2) After using the decision making learning model the average score of students increased, namely 82.54, and the highest score obtained by students after using the decision making learning model was 92, (3) Based on this research, the results of the hypothesis calculation using the t test ( Paired Sample T Test ) at a significant level of 0.05 obtained the sig. (2-tailed) is 0.000 ≤ 0.05, it can be said to be accepted and rejected. The results of the analysis of the data can be concluded that there is a significant difference between the pretest and posttest , thus there is an influence of the decision making learning model on the writing skills of class IV students of UPT SDN 060890 Medan Polonia..